Design and Electrical Characterization of Plant Microbial Fuel Cell (PMFC) Using Eichhornia crassipes by Varying the Electrode Distance and Effect Light of the Sun - Suryani, Mei; Pauzi, Gurum Ahmad; Junaidi, Junaidi; Suciyati, Sri Wahyu (Departement of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2024)
The Plant Microbial Fuel Cell (PMFC) design using water hyacinth has been successfully created. The PMFC was then treated by varying the distance of the electrode and giving the effect of sunlight. The electrodes used are Cu-Zn pairs where the electrode distance varies, with values of 3, 6, 9, and 12 cm. Furthermore, the data was taken with PMFC conditions placed outside and indoors for 14 days (331 hours). The results showed that PMFC with an electrode distance of 3 cm produced a more excellent value of electrical power than the other electrode distances, which was 0.6786 mW on the second day at the 37th hour or in the afternoon at 13.00 WIB. In general, the electrical characteristics produced by PMFCs, which are affected by sunlight, produce greater electrical power than PMFCs indoors.